FUNCTIONAL-SEMANTIC FEATURES OF BARBARISMS USED IN ENGLISH (Scientific journal of the Fergana State University, 2023)
The use of barbarisms in the article is aimed not at a writer or a speaker but to introduce elements of a new language, a new world, a new culture that is familiar or unfamiliar to the listener or reader during the communicative function of the language and thereby introduce it into a new language, culture and to the new world.